Overlap of proteomics biomarkers between women with pre-eclampsia and PCOS: a systematic review and biomarker database integration - Khan, Gulafshana Hafeez; Galazis, Nicolas; Docheva, Nikolina; Layfield, Robert; Atiomo, William (Oxford University Press, 2014)
Study question: Do any proteomic biomarkers previously identified for pre-eclampsia (PE) overlap with those identified in women with polycystic ovary syndrome (PCOS). Summary answer: Five previously identified proteomic biomarkers were found to be common in women with PE and PCOS when compared with controls.